Comparative study on superplastic tensile behaviors of the as-extruded Ti6Al4V alloys and TiBw/Ti6Al4V composites with tailored architecture. (5th March 2016) - Huang, L.J.; Lu, C.J.; Yuan, B.; Wei, S.L.; Cui, X.P.; Geng, L.
Abstract: The superplastic tensile behaviors and mechanisms of Ti6Al4V alloys and TiBw/Ti6Al4V composites with tailored architecture were comparatively studied in order to reveal the superplasticity mechanisms. The superplastic tensile tests were carried out at the temperatures of 900 °C, 925 °C, 950 °C and 975 °C with the strain rate of 0.000316/s, 0.001/s and 0.00316/s, respectively. The composites exhibited higher superplasticity, higher strain rate sensitivity index m and lower activation energy Q than the alloys. This might be attributed to the small lamellar aspect ratio and TiBw reinforcement addition. Microstructural observation showed that the aspect ratio of α phase in the Ti6Al4V alloys decreased with increasing strains, and transferred to equiaxed grains only in the tip area. Therefore, necking could not be constrained and transferred to other positions with unfavorable microstructure, led to the needle-like fracture macro morphology. On the contrary, the TiBw/Ti6Al4V composites had weak necking tendency due to the globalization process completed at small strain, which contributed to the large elongations. Recrystallization should be responsible for the decrease in lamellar aspect ratio and increase in volume fraction of β phase, which are considered to be the major coordination mechanism of superplasticity for the as-extruded TiBw/Ti6Al4V composites. Graphical abstract: The microstructure evolution of the as-extruded TiBw/Ti6Al4V composites during superplastic tensile tests: (a) grip area, (b) near grip area, (c) near tip area and (d) tip area. Highlights: The composites abnormally exhibit higher superplasticity than the alloys. The composite superplasticity mechanisms are grain boundary sliding and dynamic recrystallization. The composites with tailored architecture have weaker necking tendency than the alloys.